2022
DOI: 10.3390/coatings12010103
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Black Cotton Soil Stabilization with Natural Lime and Pozzolans in Pavement Subgrade Construction

Abstract: This study explores the engineering characteristics of Black cotton soil (BCS) stabilized with natural lime, volcanic ash (VA), and their mixtures. Based on the available literature, the stabilization of VA-BCS is limited. Laboratory tests conducted on stabilized BCS include the Atterbeg limits, the proctor test, the swell percent test, and the California bearing ratio (CBR). The results showed that adding VA and lime greatly improves the engineering characteristics of BCS. BCS stabilized with a mixture of VA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Therefore, increasing the optimal soil moisture in samples stabilized with lime occurs due to the hydration and pozzolanic reaction between soil and lime, as well as the hydrophilicity of lime [18]. Additionally, the drop in density is associated to the replacement of particles [64]. According to the results, adding lime to clay soil increases the UCS and CBR of the soil, which was in line with the results of other studies [62,65].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, increasing the optimal soil moisture in samples stabilized with lime occurs due to the hydration and pozzolanic reaction between soil and lime, as well as the hydrophilicity of lime [18]. Additionally, the drop in density is associated to the replacement of particles [64]. According to the results, adding lime to clay soil increases the UCS and CBR of the soil, which was in line with the results of other studies [62,65].…”
Section: Discussionsupporting
confidence: 88%
“…It should be noted that the short-term strength of the soil stabilized with lime is due to the cation exchange reaction and the long-term strength is due to the pozzolanic reaction [67]. Yin et al [64] also mentioned that increasing CBR values are related to cations and the pozzolanic reaction between soil and lime. In addition, previous studies indicated that the pozzolans have no cementing value unless mixed with lime in the presence of water [54,68].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a soil sample was mixed with FA at percentages of 5%, 10%, 15%, and 20%, and rice husk ash at percentages of 10%, 15%, 20%, and 25%. [21] analyzed technical properties of BCS stabilized with natural lime, Volcanic Ash (VA), and a mixture of the two. The results showed that the engineering properties of BCS were greatly improved by the addition of VA and lime.…”
Section: Literature Of Reviewmentioning
confidence: 99%
“…Although many studies have been reported on soil stabilization with traditional binders, such as cement or slag, the literature is not sufficiently includes reports on use of blended binders. The existing studies report, the use of polypropylene and silica fume blended combination for improving strength characteristics of black cotton soil [23], the mixtures of natural lime and volcanic ash for black cotton soil stabilization [24] and or the use of coal bottom ash for stabilization of expansive soils using stabilizing agent CBA [25].…”
Section: Sonic Testsmentioning
confidence: 99%